Thiamine administration may increase survival benefit in critically ill patients with myocardial infarction - Yue, Suru; Wang, Jia; Zhao, Yumei; Ye, Enlin; Niu, Dongdong; Huang, Jiasheng; Li, Xiaolin; Hu, Yiling; Hou, Xuefei; Wu, Jiayuan (Frontiers in Nutrition, 2023)
Background: Myocardial infarction (MI) is a common cardiovascular disease (CVD) in critically ill patients, leading to 17% mortality in the intensive care unit (ICU) setting. Patients with CVD frequently suffer from thiamine insufficiency, thereby thiamine supplements may be helpful. Unfortunately, the relationship between thiamine treatment and survival outcomes in ICU patients with MI is still unknown.The purpose of the research is to demonstrate the survival advantage of thiamine application in these patients.The Medical Information Mart of Intensive Care-Ⅳ database served as the foundation for this retrospective cohort analysis. Depending on whether patients were given thiamine therapy during the hospital stay, critically ill MI patients were split into the thiamine and non-thiamine groups. The Kaplan-Meier (KM) method and Cox proportional hazard models were used to evaluate the relationship between thiamine use and the risk of in-hospital, 30-day, and 90-day mortality. To validate the results, a 1:2 closest propensity-score matching (PSM) was also carried out.Results: This study included 1782 patients for analysis with 170 and 1612 individuals in the thiamine and non-thiamine groups, respectively. The KM survival analyses revealed that the risk of in-hospital, 30-day, and 90-day mortality was significantly lower in the thiamine group than the none-thiamine group. After modifying for a variety of confounding factors, the Cox regression models demonstrated substantial positive impacts of thiamine use on in-hospital, 30-d, and 90-d mortality risk among critically ill patients with MI with hazard ratio being 0.605 [95% confidence interval (CI): 0.397-0.921, P = 0.019], 0.618 (95% CI: 0.398-0.960, P = 0.032), and 0.626 (95% CI: 0.411-0.953, P = 0.028), respectively, in the completely modified model. PSM analyses also obtained consistent results.Thiamine supplementation is related to a decreased risk of mortality risk in critically ill patients with MI who are admitted to the ICU. More multicenter, 3 large-sample, and well-designed randomized controlled trials are needed to validate this finding.